Sistem Deteksi Kebakaran Menggunakan Sensor Asap Dan Sensor Api Berbasis Nodemcu Esp8266 Pada PAUD Mandiri - Fachrurozi Alwi; Ahmad Chusyairi (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Bina Insani, 2022)
Fire is a disaster that we often encounter on television news, or direct events that are heard by our eyes and ears so that the impact of this fire will be quite detrimental to the building material sector, to suffer financial losses from the impact of a fire disaster. For this reason, this writing aims to make a fire detection system tool using a prototype method based on the nodemcu esp8266 by providing warning information about a fire on the buzzer sensor and led light. If there is a concentration of smoke or a fire is detected in the PAUD Mandiri. Then the nodemcu esp8266 microcontroller which is connected to Wi-Fi has the role of sending fire warning notification information via email application with the help of the Thinger io platform. In designing a fire detection system prototype using the components of the Nodemcu Esp8266 Microcontroller, Smoke Sensor, Fire Sensor, Buzzer, Led Light, and 16x2 LCD. The expected results in the Fire Detection System Prototype Research Using Smoke Sensors and Fire Sensors Based on Nodemcu Esp8266 in PAUD Mandiri are that the system can function properly and as expected. If the system detects smoke and the appearance of a flame in the PAUD Mandiri classroom, the buzzer sensor, the LED light will light up as a warning indicator of a fire and provide notification information about a fire warning via the user's email. Keywords: Nodemcu Esp8266, Smoke Sensor, Flame Sensor